Endocannabinoids effect on oxidative status of human platelets. Issue 1 (19th October 2022) - Signorello, Maria Grazia; Ravera, Silvia; Leoncini, Giuliana
Abstract: Reactive oxygen species (ROS) are known to regulate platelet activation. Since endocannabinoids behave as platelet agonists, we investigated the effect of two endocannabinoids, 2‐arachidonoylglycerol (2AG) and anandamide (AEA) on the oxidative status of human platelets. We have demonstrated that 2AG and AEA stimulate ROS production, superoxide anion formation and lipid peroxidation. The effect is dose and time dependent and mainly occurs through the involvement of cannabinoid receptor 1 (CB1) since all tested parameters are greatly reduced by SR141716, the CB1 specific inhibitor. The specific inhibitor of cannabinoid receptor 2 (CB2) SR144528 produces a very small inhibition. The involvement of syk/PI3K/AKT/mTor pathway in oxidative stress induced by endocannabinoids is shown. Nicotinamide adenine dinucleotide phosphate oxidase seems to be poorly involved in the endocannabinoids effect. Concerning the aerobic metabolism, it has been demonstrated that endocannabinoids reduce the oxygen consumption and adenosine triphosphate synthesis, both in the presence of pyruvate + malate or succinate. In addition, endocannabinoids inhibit the activity of respiratory complexes II, III and IV and increase the activity of respiratory complex I. The endocannabinoids effect on aerobic metabolism seems to be also a CB1 mediated mechanism. Thus, in human platelets oxidative stress induced by endocannabinoids, mainly generated in the respiratory chain through the activation of complex I and the inhibition of complex II, III and IV, may lead to thrombotic events, contributing to cardiovascular diseases.